1991
DOI: 10.1002/clc.4960141204
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the combination of low‐dose mexiletine and metoprolol on ventricular arrhythmia

Abstract: Summary: Antiarrhythmic drug therapy is often ineffective or poorly tolerated. Combining antiarrhythmic agents with different electrophysiologic properties may have a synergistic antiarrhythmic effect when compared with each drug alone. If a lower dose of each drug can be used, combination therapy may also result in lower incidence of side effects. 'The goal of our study was to assess the complementary effect of low-dose mexiletine and metoprolol, when compared with either drug alone. Ten patients with frequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“… 49 , 54 , 57 , 58 , 62 , 65 , 66 , 97 , 125 , 126 , 139 , 155 , 180 , 181 , 189 In all of the studies reporting on left ventricular ejection fraction, 14 (93.3%) of the studies (475 of 476 patients) showed no negative effects of mexiletine on left ventricular ejection fraction. 49 , 54 , 57 , 58 , 62 , 65 , 66 , 97 , 125 , 126 , 155 , 180 , 181 , 189 Three (20%) studies comprising 36 patients reported on right ventricular ejection fraction, and none of these studies demonstrated a decrease in right ventricular ejection fraction. 66 , 125 , 126 …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“… 49 , 54 , 57 , 58 , 62 , 65 , 66 , 97 , 125 , 126 , 139 , 155 , 180 , 181 , 189 In all of the studies reporting on left ventricular ejection fraction, 14 (93.3%) of the studies (475 of 476 patients) showed no negative effects of mexiletine on left ventricular ejection fraction. 49 , 54 , 57 , 58 , 62 , 65 , 66 , 97 , 125 , 126 , 155 , 180 , 181 , 189 Three (20%) studies comprising 36 patients reported on right ventricular ejection fraction, and none of these studies demonstrated a decrease in right ventricular ejection fraction. 66 , 125 , 126 …”
Section: Resultsmentioning
confidence: 98%
“…In 40 (18%) studies, worsening or not worsening of arrhythmias is actively mentioned. 27 , 31 , 34 , 38 , 39 , 41 , 50 , 54 , 55 , 57 , 58 , 60 , 62 , 64 , 68 , 75 , 76 , 85 , 87 , 90 , 106 , 118 , 128 , 129 , 138 , 141 , 151 , 154 , 161 , 164 , 166 , 174 , 175 , 183 , 201 , 207–209 , 213 , 218 In total, in this subset of 40 studies, in 137 of 2173 (6.3%) patients, the arrhythmia worsened after start of mexiletine.…”
Section: Resultsmentioning
confidence: 99%